Perspectives on Intercultural Contact and Japanese Learning by Indonesian Trainees in Japan - Lisda Nurjaleka (Universitas Gadjah Mada, 2022)
Intercultural Contact (Hereafter IC) is when two or more people from different cultural backgrounds carry out socio-economic or political exchanges in one contact zone. Intercultural contact is possible to appear everywhere and by one. Intercultural contact concerning immigrants, either as students or workers abroad. This study aims to investigate the intercultural contact of Indonesian workers, focusing on trainees (Jjisshusei) in Japan. International workers face cross-cultural communication with co-workers or domestic workers. The trainees as respondents in this study are sent to Japan as a form of on-the-job training in collaboration between the Indonesian government and the Japanese. The trainees were exposed to the Japanese language, culture, society, and economy. Therefore, their cultural competence is essential. This study examines intercultural communication in the trainee’s community, mainly focusing on how intercultural contact occurs between trainees and Japanese residents. The result showed that apart from the trainees’ understanding of the importance of learning Japanese, they still lack experience in communicating with Japanese locals besides their co-workers. This study contributes to second language learning in intercultural understanding and L2 learners’ identity.